2010
DOI: 10.1097/qai.0b013e3181c990bf
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Atazanavir/Ritonavir Compared With Twice-Daily Lopinavir/Ritonavir, Each in Combination With Tenofovir and Emtricitabine, for Management of Antiretroviral-Naive HIV-1–Infected Patients: 96-Week Efficacy and Safety Results of the CASTLE Study

Abstract: Noninferiority of atazanavir/ritonavir to lopinavir/ritonavir was confirmed at 96 weeks. Atazanavir/ritonavir had a better lipid profile and fewer gastrointestinal adverse events than lopinavir/ritonavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
150
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(169 citation statements)
references
References 24 publications
15
150
0
4
Order By: Relevance
“…34,58 Similar to the results obtained here, safety results from ARTEMIS suggested low rates of grade 2-4 AEs, including gastrointestinal and renal AEs, in subjects receiving DRV/r over 96 weeks. 39 Subjects receiving DRV/r in ARTEMIS had a significantly lower rate of diarrhea compared with LPV/r subjects (4% vs. 11%, respectively) and, in line with results from this trial, no clinically relevant changes were seen in creatinine clearance in either treatment arm.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…34,58 Similar to the results obtained here, safety results from ARTEMIS suggested low rates of grade 2-4 AEs, including gastrointestinal and renal AEs, in subjects receiving DRV/r over 96 weeks. 39 Subjects receiving DRV/r in ARTEMIS had a significantly lower rate of diarrhea compared with LPV/r subjects (4% vs. 11%, respectively) and, in line with results from this trial, no clinically relevant changes were seen in creatinine clearance in either treatment arm.…”
Section: Discussionsupporting
confidence: 74%
“…32,33 Another PI, atazanavir (ATV; REYATAZ, Bristol-Myers Squibb, Princeton, NJ), boosted with low-dose ritonavir (ATV/r), has also demonstrated a favorable metabolic profile in treatment-naive subjects. 34 The metabolic effects of DRV/r have been shown to be comparable with those of ATV/r in HIV-negative subjects. 33 Furthermore, the metabolic effects of these ARVs have not been directly compared in HIV-1-infected, treatmentnaive subjects.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…While adverse events were the main known reason for discontinuation, the long-term safety profile in this real-life study was consistent with that observed previously in clinical trials of up to 2 years duration, [5][6][7] with no new or unexpected adverse events identified.…”
Section: Jansen Et Alsupporting
confidence: 69%
“…Several PI agents are now available, providing options for individualized therapy, and most regimens are boosted with the pharmacological enhancer, ritonavir. 2 In clinical trials, convenient once-daily ritonavir-boosted atazanavir (ATV/r)-based regimens have proven efficacy and safety in both treatment-naive [3][4][5] and -experienced patients. 6,7 These regimens are recommended as a preferred therapeutic option for initiation of therapy in treatment-naive patients by the current treatment guidelines in both the United States 8,9 and Europe.…”
mentioning
confidence: 99%